POWER SHIFTING AND THE CHALLENGES OF PRESIDENTIAL SYSTEM IN INDONESIA (1945-2019) - Dara Purnama; Muhammad Naufal; Kamal Muntaha Ahmad (Jurnal PPI Dunia, 2021)
The dynamics of government system in Indonesia has a long way road since Indonesia secure their independence in 1945. Acco rding to Indonesia constitution, Indonesia adhere the presidential system. Yet, in practice the government system in Indonesia seems more like a Parliamentary system. During the period of 1945-1959, The presidential system in Indonesia doesn’t have any places to operate, entered the guided democracy era, the presidential system obtain its first place. Seeing that, the president success to obtain their power and became a dictator, after Sukarno was remove from the office, Indonesia entered the “new order” regime. This regime just like guided democracy era, the President became center of the power because president was choosed by the parliament and most the fellow comes from the party government. After reformasi in 1998, the presidential system has their own challenges. Considering, the multyparty system felt is not compatible with the presidential system. Hence, as long as Indonesia established, the presidential system in Indonesia has their own dynamic and challenges. Every regime has their own dynamic and challenges. This article aims to provide a study to strengthen the presidential system and using a qualitative approach based on a comprehensive literature review.